2018
DOI: 10.1101/472613
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting IDH1 as a pro-senescent therapy in high-grade serous ovarian cancer

Abstract: Epithelial ovarian cancer (EOC) is the deadliest gynecological cancer. High-grade serous carcinoma (HGSC) is the most frequently diagnosed and lethal histosubtype of EOC. A significant proportion of HGSC patients relapse with chemoresistant disease.Therefore, there is an urgent need for novel therapeutic strategies for HGSC. Metabolic reprogramming is a hallmark of cancer cells, and targeting metabolism for cancer therapy may be beneficial. Here we found that in comparison to normal fallopian tube epithelial c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Using two independent HGSOC cells carrying wildtype ATM ( cbioportal.com ), we found that inhibition of ATM using two small molecule inhibitors (KU60019 and AZD0156) synergized with fenofibrate in multiple HGSOC cell lines to decrease colony formation ( Figure 4 A, B). While cell death, as determined by 7AAD staining, was not affected ( Figure 4 C), we observed multiple senescence markers, including increased SA-β-Gal and PML bodies and decreased lamin B1 expression [ 18 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] in the combination treated cells ( Figure 4 D, E). Together, these data demonstrate that the combination of ATM inhibition and fenofibrate treatment is synergistic in HGSOC through induction of senescence.…”
Section: Resultsmentioning
confidence: 87%
“…Using two independent HGSOC cells carrying wildtype ATM ( cbioportal.com ), we found that inhibition of ATM using two small molecule inhibitors (KU60019 and AZD0156) synergized with fenofibrate in multiple HGSOC cell lines to decrease colony formation ( Figure 4 A, B). While cell death, as determined by 7AAD staining, was not affected ( Figure 4 C), we observed multiple senescence markers, including increased SA-β-Gal and PML bodies and decreased lamin B1 expression [ 18 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] in the combination treated cells ( Figure 4 D, E). Together, these data demonstrate that the combination of ATM inhibition and fenofibrate treatment is synergistic in HGSOC through induction of senescence.…”
Section: Resultsmentioning
confidence: 87%
“…Recent data from HGSOC patients suggest that senescence occurs in vivo after therapy and is associated with a better outcome (46). Indeed, other publications have also indicated that senescence is a beneficial therapeutic response (47,48,(60)(61)(62)(63). The mechanism of senescence induction by the combination of ATM inhibition and fenofibrate remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Cell survival assays: Cell survival in response to knockdowns and enzalutamide was assessed using crystal violet staining. The crystal violet staining protocol was used as previously described [19]. In brief, 1x10 4 cells were seeded per well in 100uL RPMI 1640 with L-glutamine in 10% fetal bovine serum and underwent described drug treatments with eight biological replicates.…”
Section: Quantitative Pcr (Qpcr): Total Rna Was Extracted From Cells mentioning
confidence: 99%